2020
DOI: 10.1038/s41598-020-59245-3
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent overweight and obesity and the risk of papillary thyroid cancer in adulthood: a large-scale case-control study

Abstract: this study aimed to investigate the association between adolescent overweight and obesity and ptc risk in adulthood. We conducted a case-control study in the Republic of Korea with 1,549 PTC patients and 15,490 controls individually matched for age and sex. We estimated body mass index (BMI) at age 18 years from self-reported weight at this age. Compared with BMI < 23.0 at age 18 years, BMI ≥ 25.0 at age 18 years was associated with higher PTC risk (odds ratio [OR] = 4.31, 95% confidence interval [CI]: 3.57, 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…Kim and coworkers conducted a case-control study in the young Korean population (18 years old) and showed that both men and women with BMI ≥ 25 had a higher risk of developing PTC than those with BMI < 23 [33].…”
Section: Relationship Between Obesity and Thyroid Cancermentioning
confidence: 99%
“…Kim and coworkers conducted a case-control study in the young Korean population (18 years old) and showed that both men and women with BMI ≥ 25 had a higher risk of developing PTC than those with BMI < 23 [33].…”
Section: Relationship Between Obesity and Thyroid Cancermentioning
confidence: 99%
“…Recent studies are also reporting that obesity is associated with increased incidence of thyroid cancer [21]. Kim et al [21].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies are also reporting that obesity is associated with increased incidence of thyroid cancer [21]. Kim et al [21]. Performed a case-control study in which the authors hypothesized that overweight and obesity would be associated with higher risk of PTC in an adolescent Korean population (BMI≥25 at age 18 years).…”
Section: Discussionmentioning
confidence: 99%
“…A case‐control study in the Republic of Korea provided moderate evidence that overweight and obesity in adolescence were correlated with high PTC risk in adulthood, and the association between obesity in adolescence at age 18 years and PTC risk in adulthood was stronger in men than in women 34 . In addition to BMI, a cohort study also showed that taller height during childhood and adolescence was associated with an increased risk of adult TC 35 .…”
Section: Introductionmentioning
confidence: 99%
“…Among TC survivors in a case‐control study, obesity at age 18 years was associated with cancer‐related aggressive behavior later in life, such as extrathyroidal extension and tumor size, 34 and excess body fatness in early life will increase adverse overcomes in TC survivors. A higher BMI in TC survivors was positively associated with a higher recurrence risk of TC 37 .…”
Section: Introductionmentioning
confidence: 99%